Diseño de indumentaria que aumenta la fricción de agarre y evita las quemaduras de primer grado en la piel ocasionadas por la práctica deportiva “Pole sport” - Mera Naranjo, Natalia (Universidad Antonio Nariño, 2022)
The objective of this project is the development of an object system based on industrial design focused on clothing, which increases grip friction and prevents first-degree skin burns caused by "pole" sports practice, where the activity will be analyzed. current physics of pole dance and specifically pole sport” that is practiced as a sport and competition in Colombia. The clothing is developed from the analysis of biomimicry or biomimetics, inspired by nature, with references such as the tree frog and its characteristics, as a source of innovation, allowing the development of this activity, thus breaking better precision and protection in practitioners.